Lung Transplant Candidates With Pretransplant Gastroesophageal Reflux and Antibodies to Lung Self-antigens Have Shorter CLAD-free Survival After Transplant. Issue 3 (11th February 2022) - Razia, Deepika; Mittal, Sumeet K.; Bansal, Sandhya; Ravichandran, Ranjithkumar; Smith, Michael A.; Walia, Rajat; Bremner, Ross M.; Mohanakumar, Thalachallour; Tokman, Sofya
Abstract : Background: Pre–lung transplant (LTx) gastroesophageal reflux (GER) and circulating antibodies against the lung self-antigens (SAbs) collagen V and K-alpha-1 tubulin may predispose recipients to chronic lung allograft dysfunction (CLAD). We aimed to study the association of pre-LTx GER or pre-LTx SAbs with CLAD. Methods: In this retrospective analysis of patients who underwent LTx between 2015 and 2019, pre-LTx GER and SAbs were dichotomously defined as present or absent. The study group comprised recipients with either GER‚ SAbs, or both, and the control group comprised recipients without GER or SAbs. Endpoints included CLAD and survival. Results: Ninety-five LTx recipients were divided into a study group (n = 71; 75%) and a control group (n = 24; 25%). Pretransplant GER was associated with pre-LTx SAbs (odds ratio [95% confidence intervals], 5.022 [1.419-17.770]; P = 0.012). In addition, the study group (either GER‚ SAbs, or both) had a higher risk of CLAD (hazard ratio [95% confidence intervals], 8.787 [1.694-45.567]; P = 0.010) and lower CLAD-free survival after LTx than the control group ( P = 0.007); however, overall survival was similar between the 2 groups ( P = 0.618). Conclusions: GER was associated with elevated SAbs in LTx candidates, and either GER, SAbs, or both were associated with CLAD in LTx recipients. This association suggests that GER may cause an immune response to normally sequestered lung-associated self-antigens that drives ongoing lung injury.